2012
DOI: 10.18517/ijaseit.2.6.238
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Benefits and Barriers of E-Procurement: Malaysian SMEs Perspective

Abstract: Procurement is one of the major aspects for an enterprise to improve its supply chain management and hence enterprise performance. The advent of Internet has introduced e-commerce and drastically changing the way procurement is done to improve operation efficiency and reduce transaction cost significantly. Thereby, this lead to the term "e-procurement" or "e-purchasing". However, many Small and Medium Enterprises (SMEs) still perceive e-procurement as infeasible although e-procurement is introduced in the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…E-procurement is an 'umbrella term' [Fleming et al, (2010), p.232] that encompasses several elements, including electronic ordering, internet bidding, purchasing cards, reverse auctions, and integrated automatic procurement systems (Moon, 2005;George et al, 2011). E-procurement has been recently receiving much attention from businesses, industries and governments as it is reportedly become a powerful tool to improve effectiveness and efficiencies as well as service quality of its adopters (Basheka et al, 2012;Eei et al, 2012) and its application is nowadays inevitable in both manufacturing and services, not also in the private but also in the public sector (Gunasekaran and Ngai, 2008;Schiele, 2007). Companies have moved to e-procurement platforms, where transactions are done efficiently and in a fast pace (Makinen et al, 2011).…”
Section: E-procurement Definition and Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…E-procurement is an 'umbrella term' [Fleming et al, (2010), p.232] that encompasses several elements, including electronic ordering, internet bidding, purchasing cards, reverse auctions, and integrated automatic procurement systems (Moon, 2005;George et al, 2011). E-procurement has been recently receiving much attention from businesses, industries and governments as it is reportedly become a powerful tool to improve effectiveness and efficiencies as well as service quality of its adopters (Basheka et al, 2012;Eei et al, 2012) and its application is nowadays inevitable in both manufacturing and services, not also in the private but also in the public sector (Gunasekaran and Ngai, 2008;Schiele, 2007). Companies have moved to e-procurement platforms, where transactions are done efficiently and in a fast pace (Makinen et al, 2011).…”
Section: E-procurement Definition and Benefitsmentioning
confidence: 99%
“…Hawking et al (2004) researched SME in Australia and found that one of the main inhibitors was the absence of a single e-procurement solution. In a similar study, Eei et al (2012) identified internal and external barriers to the implementation of e-procurement in Malaysian SME. Karjalainen and Kemppainen (2008) used data from Finnish SMEs to conclude that availability of resources, company size and e-systems explained the level of SEM involvement.…”
Section: P E-p Adoption Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other literature discussed the key benefits of e-procurement including perceived direct benefits Chang, Wang & Chiu, 2008;Croom & Brandon-Jones, 2007;Gunasekaran & Ngai, 2008;Ho et al, 2008;Vaidyanathan & Devaraj, 2008) that help to identify different key factors of better performance of public or private organizations including perceived direct benefits of e-procurement (Brandon-Jones & Carey, 2011;Mitchell, 2000;Panayiotou, Gayialis & Tatsiopoulos, 2004), perceived indirect benefits of e-procurement (Gunasekaran et al, 2009), perceived cost, firm size, top management support, information sharing culture, business partner influences (Teo, Lin & Lai, 2009). Eei, Husain & Mustaffa (2012) identified e-procurement's potential tangible and intangible benefits including enhanced efficiency and effectiveness in an organisation through reductions in costs and procurement process cycle times, increased transparency in contracts and overall competitiveness E-procurement has been recognised as a core application in e-commerce / e-government . Research on combating corruption or anti-corruption includes: E-government as an anticorruption tool (Andersen, 2008), e-government for improved public sector service delivery in India, Ethiopia and Fiji , applying E-government Information System for Anti-corruption strategy ), e-government, Transparency and Anti-corruption (Fan,Zhang & Yue, 2009), anticorruption effects of information communication and technology and social capital (Shim & Eom, 2009), using ICT to combat corruption-tools, methods and results (Grönlund et al, 2010), and an institutional analysis of an e-government system for anti-corruption: the case of Online Procedures Enhancement for civil application (OPEN) (Kim et al, 2009).…”
Section: Anti-corruption Factors Some Key Referencesmentioning
confidence: 99%
“…Among these factors, Rezgui et al 25 observed that organizational issues are among the key factors affecting the adoption of new technologies in the construction sector. Al-Moala and Li 26 and Tran and Huang 27 also corroborated this by noting that organisational issues play key roles in determining the extent, success, and impact of e-procurement use. This is because the decision to adopt new technologies and processes such as e-procurement is usually within the purview of organizations' top management, as explained by Ibem et al 24 and Eei et al 28 In spite of the growing body of knowledge on e-procurement use in the procurement of building and infrastructure projects, the extent of its adoption in the Nigerian building industry is not clearly understood.…”
Section: Introductionmentioning
confidence: 75%